Nano-QTTR development for interspecies aquatic toxicity of silver nanoparticles between daphnia and fish. (November 2021) - Jung, Ukhyun; Lee, Byongcheun; Kim, Geunbae; Shin, Hyun Kil; Kim, Ki-Tae
Abstract: Limited studies of quantitative toxicity-toxicity relationship (QTTR) modeling have been conducted to predict interspecies toxicity of engineered nanomaterials (ENMs) between aquatic test species. A meta-analysis of 66 publications providing acute toxicity data of silver nanoparticles (AgNPs) to daphnia and fish was performed, and the toxicity data, physicochemical properties, and experimental conditions were collected and curated. Based on Euclidean distance (ED) grouping, a meaningful correlation of logarithmic lethal concentrations between daphnia and fish was derived for bare (R 2 bare = 0.47) and coated AgNPs (R 2 coated = 0.48) when a distance of 10 was applied. The correlation of coated AgNPs was improved (R 2 coated = 0.55) by the inclusion of descriptors of the coating materials. The correlations were further improved by R 2 bare = 0.57 and R 2 coated = 0.81 after additionally considering particle size only, and by R 2 bare = 0.59 and R 2 coated = 0.92 after considering particle size and zeta potential simultaneously. The developed ED-based nano-QTTR model demonstrated that inclusion of the coating material descriptors and physicochemical properties improved the goodness-of-fit to predict interspecies aquatic toxicity of AgNPs between daphnia and fish. This study provides insight for future in silico research on QTTR model development in ENM toxicology. Graphical abstract: Image 1 Highlights: Quantitative toxicity-toxicity relationship model is developed for interspecies ecotoxicity of AgNPs. Euclidean distance grouping is applied to derive a meaningful correlation of aquatic toxicity of AgNPs between daphnia and fish.. The correlation is suggested for bare- and coated AgNPs, respectively. The correlation of coated AgNPs is improved when descriptors of coating materials are considered. The correlation of coated AgNPs is further improved when the primary size and zeta-potential are considered.